KUALIFIKASI PENGGUNAAN SENJATA KIMIA PADA KONFLIK BERSENJATA DI SURIAH DARI PERSPEKTIF HUKUM HUMANITER INTERNASIONAL: QUALIFICATION OF CHEMICAL WEAPONS IN ARMED CONFLICT IN SYRIA FROM THE PERSPECTIVE OF INTERNATIONAL HUMANITARIAN LAW - Fajwa, R. Halya Zayna; Wibowo, Aji (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2024)
The conflict in Syria is part of the series of Arab revolutions that occurred in 2011  due to opposition to the regime of President Bashar al-Assad, evolving into armed  rebellion. The conflict reached its peak when battles involving chemical weapons  were discovered in Ghouta in August 2013, resulting in numerous casualties. This  has qualified as war crimes and serious violations from the perspective of  international humanitarian law. This research is a literature study using data  analysis methods. Based on the data obtained, the use of chemical weapons in this  warfare has violated the rules of the Organization for the Prohibition of Chemical  Weapons and international humanitarian law agreements.